PENTINGNYA LITERASI DIGITAL DALAM MEMPERSIAPKAN SISWA MENGHADAPI ERA SOCIETY 5.0 - SITI CHUSNUL CHOTIMAH; SARI ANGGREINI; AGUS SULISTYO (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
In the era of Society 5.0, humans and digital technology must work together in various aspects of life, such as education. The purpose of this study is to find out how prepared students are to face the challenges and opportunities offered by the modern era through digital literacy. The method used in this study is a literature study by reviewing literature related to digital literacy and student readiness. The results of the study show that digital literacy plays an important role in maximizing students' potential to face the Society 5.0 era. The ability to access, assess, and use digital data is included in this capability. To achieve the success of digital literacy in education, it is necessary to improve technological infrastructure, adjust the curriculum, and train teachers. Students who have good digital literacy are expected to be able to adapt to technological advances and play an active role in the development of a technology-based society.